Some indicators of physical state of the high school students on the stage of implementation of contents of the physical culture program - Schislovsky, S. V. (Journal of Education, Health and Sport, 2015)
Information of the documentary materials and scientific literature related to the efficiency of the contents of the current physical culture program in solving one of its major objectives, namely improving of physical state, was analyzed. A very low efficiency of the content for the studied parameters of physical state of high school boys was found. Only explosive and absolute muscle strength improves in the period of 15-17 years, largely due to the sensitive period of development of these qualities. Parameters of the other physical qualities, as well as overall physical performance, virtually remain unchanged and slightly expressed. In connection with the obtained data, the issue of improving the methods of influence on the physical state of high school students for its enhancement at the classes of physical education, becomes actualized.